Masterpieces from the Museum of Fine Arts, Houston director's choice (Museum of Fine Arts, Houston, 2009)
"Peter C. Marzio, director of the Museum of Fine Arts, Houston, presents his 100 favorite masterpieces drawn from the museum's collection of nearly 60,000 works. Informative descriptions of the artworks by the museum's curatorial staff complement Dr. Marzio's own, highly personal, commentary on what a masterpiece means to him"--Provided by publisher.